2018
DOI: 10.3762/bjnano.9.72
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of a ZnO–BiOI p–n nano-heterojunction with excellent visible-light photocatalytic activity

Abstract: In this paper, an efficient method to produce a ZnO/BiOI nano-heterojunction is developed by a facile solution method followed by calcination. By tuning the ratio of Zn/Bi, the morphology varies from nanoplates, flowers to nanoparticles. The heterojunction formed between ZnO and BiOI decreases the recombination rate of photogenerated carriers and enhances the photocatalytic activity of ZnO/BiOI composites. The obtained ZnO/BiOI heterostructured nanocomposites exhibit a significant improvement in the photodegra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Most of the literature in this field is focused on enhancing the RE-emission extraction, by out-coupling guided light via Bloch mode resonances of a PC, which leads to an increase in luminescence by a factor of several times. [24][25][26] In a previous study using a Ce 3+ , Pr 3+ , Yb 3+ tri-doped CaYAlO4 layer, we theoretically demonstrated that Bloch mode resonances at excitation wavelengths can lead to a 10-fold increase of the UV light absorption. 27 Most recently, Hofmann et al have proposed a one dimensional (1D) PC design which combines absorption improvement and LDOS enhancement, yielding a 480-fold theoretical up-conversion enhancement of Er 3+ doped NaYF4.…”
mentioning
confidence: 88%
“…Most of the literature in this field is focused on enhancing the RE-emission extraction, by out-coupling guided light via Bloch mode resonances of a PC, which leads to an increase in luminescence by a factor of several times. [24][25][26] In a previous study using a Ce 3+ , Pr 3+ , Yb 3+ tri-doped CaYAlO4 layer, we theoretically demonstrated that Bloch mode resonances at excitation wavelengths can lead to a 10-fold increase of the UV light absorption. 27 Most recently, Hofmann et al have proposed a one dimensional (1D) PC design which combines absorption improvement and LDOS enhancement, yielding a 480-fold theoretical up-conversion enhancement of Er 3+ doped NaYF4.…”
mentioning
confidence: 88%
“…Kuang et al [19] reported the growth of ZnO-NR on fluorine-doped tin oxide which was decorated by BiOI nanoplatelets through a solvothermal method at 126°C, for 6 h. Other reports have published the preparation of ZnO/BiOI nanocomposites by one-pot synthesis of ZnO and BiOI precursors heated in an autoclave, also around 125°C [24] or by microwave irradiation [25]; however, reports about nanocomposites formed by ZnO nanorods decorated with BiOI micro/nanoplatelets, or with a shell of BiOI, are rare. Hence, we are reporting a simple process of preparation at room temperature of decorated ZnO nanorods by BiOI nanoplatelets through the simple dispersion of ZnO-NR in aqueous solution of 0.2 M KI and adding an aqueous solution of 0.02 M Bi(NO 3 ) 2 .…”
Section: Decoration Of Zno-nrmentioning
confidence: 99%
“…16−18 Recently, Zhang et al, reported that ZnO decorated BiOI nanosheets exhibit a 2-fold increase in photocatalytic activity for the degradation of rhodamine B (RhB) in comparison to pure BiOI. 19 Yuzhen Bu et al, demonstrated superior photocatalytic activity for MO degradation by a BiOI/MoS 2 nanocomposite due to the enhanced separation efficiency of photogenerated charge carriers. 20 Meanwhile, Wang et al, proposed that Fe doped BiOI exhibits enhanced visible light photocatalytic activity for the degradation of rhodamine B as the presence of Fe improves the electron−hole separation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, BiOI suffers from a higher recombination rate of photogenerated electrons and holes due to strong hybridization between valence band Bi 6s and O 2p orbitals which limits its photocatalytic efficiency . To improve the charge separation capability of BiOI, several strategies have been considered in the past including doping, formation of 3D- architectures, and coupling to high band gap semiconductors. Recently, Zhang et al, reported that ZnO decorated BiOI nanosheets exhibit a 2-fold increase in photocatalytic activity for the degradation of rhodamine B (RhB) in comparison to pure BiOI . Yuzhen Bu et al, demonstrated superior photocatalytic activity for MO degradation by a BiOI/MoS 2 nanocomposite due to the enhanced separation efficiency of photogenerated charge carriers .…”
Section: Introductionmentioning
confidence: 99%